Biomedical Applications of Hyaluronic Acid-Based Nanomaterials in Hyperthermic Cancer Therapy - Subin Kim; Myeong ju Moon; Suchithra Poilil Surendran; Yong Yeon Jeong (MDPI AG, 2019)
Hyaluronic acid (HA) is a non-sulfated polysaccharide polymer with the properties of biodegradability, biocompatibility, and non-toxicity. Additionally, HA specifically binds to certain receptors that are over-expressed in cancer cells. To maximize the effect of drug delivery and cancer treatment, diverse types of nanomaterials have been developed. HA-based nanomaterials, including micelles, polymersomes, hydrogels, and nanoparticles, play a critical role in efficient drug delivery and cancer treatment. Hyperthermic cancer treatment using HA-based nanomaterials has attracted attention as an efficient cancer treatment approach. In this paper, the biomedical applications of HA-based nanomaterials in hyperthermic cancer treatment and combined therapies are summarized. HA-based nanomaterials may become a representative platform in hyperthermic cancer treatment.